The Effects of the COVID-19 Pandemic on Abnormal Uterine Bleeding According to the PALM-COEIN Classification - Bektas, Onur; Bektas, Kivilcim; Aydin, Sirin; Dogan Durdag, Gulsen; Celik, Husnu (Gynecology Obstetrics & Reproductive Medicine, 2024)
OBJECTIVE: To investigate the impact of the COVID-19 pandemic on abnormal uterine bleeding (AUB) according to the PALM-COEIN classification. STUDY DESIGN: Patients who underwent surgical intervention due to AUB were categorized according to the PALM-COEIN classification, and the pandemic period was compared with the pre-pandemic period. RESULTS: During the COVID-19 pandemic, an increase in abnormal uterine bleeding (AUB) was observed. This was statistically shown to be due to ovulatory dysfunction and endometrial problems (with p-values of 0.033 and 0.024, respectively). No significant changes were detected in categories including polyp, adenomyosis, leiomyoma, malignancy, and iatrogenic causes (p>0.05). CONCLUSIONS: In the relationship between COVID-19, ovulatory dysfunction, and endometrial issues, several factors should be considered. These include direct inflammation of the ovarian and endometrial tissues, potential defects in endometrial repair mechanisms secondary to inflammation, changes in the hypothalamic-pituitary-ovarian axis, immunological effects of vaccination, systemic inflammatory responses affecting the ovary and endometrium, changes in inflammatory and immune mediators, and immune cell activation. Additionally, increased production of vasodilatory substances such as prostaglandin E2 and prostacyclin, decreased production of local vasoconstrictors like prostaglandin F2α and endothelin-1, as well as increased plasminogen activator activity leading to enhanced thrombolysis and disruptions in endometrial hemostatic mechanisms.